Effect of diet and seed pretreatment on the biology of Bruchidius uberatus (Coleoptera, Bruchidae) - El Atta, Hashim (Silva Fennica, 2000)
Diet significantly (P < 0.0001) affected fecundity of Bruchidius uberatus Fahraeus. Provision of 1% sugar solution increased fecundity from 15 eggs/female to 47. Furthermore, sugar solution prolonged significantly the oviposition period of B. uberatus from one week to two weeks. Diet also significantly (P < 0.0001) increased adult longevity. Mean adult longevity recorded was 3, 7 and 13 days in control, water and sugar treatments, respectively. Seed pretreatment had a highly significant impact on the various developmental stages of B. uberatus. Maximum egg hatchability occurred in non-husked Acacia nilotica (L.) Willd. ex Del. seeds (83%), moderate in de-husked seeds (74%) and least in seeds presoaked in concentrated sulphuric acid (42%). The frequency of larvae that developed successfully into pupae was greatest in non-husked seeds (72%), nevertheless in de-husked and acid pretreated seeds, absolutely no larvae developed into pupae and hence the adult stage was not reached in these two treatments. Thus, de-husking and acid pretreatment of A. nilotica seeds is highly recommended.